Testing Internal Control Compliance - Endang Wijayanti, Lilis; Indra Purnama, Yunus; Pw, Kristianto; Rokhmat (Dinasti International Journal of Digital Business Management, 2023)
This research investigates factors influencing compliance of the internal control. Those factors are reward, work stress and workplace. The reward and work stress are the independent variables while workplace is considered as mediating variable. Employees will perceive comfortable workplace when they see the company appreciates them and their work. Eventually, they will signal their compliance for internal control. On the other hand, when employees experience such work stress, then they will feel uneasy with their work environment, and then they will tend to decline the internal control. Research data are available from the questionnaires distributed to government officers reside at Yogyakarta. With the stepwise analysis we find that rewards positively influence the workplace and the employees compliance on the internal control. Work stress does not prove its influence on the work environment and compliance on the internal control. The workplace does not function as mediating variable.